Transformasi UMKM di Era Digital: Pelatihan dan Pendampingan Diversifikasi Produk dan Pemasaran Online pada UKM Jahe Merah Zala - Kurniawan Saputra; Joen, Deary Amethy Zahrotinufus; Saputra, Anggi; Pratomo, Panji Andhika (Batara Wisnu : Indonesian Journal of Community Services, 2025)
Zala Red Ginger SME is a micro-enterprise in South Lampung engaged in the production of processed red ginger. However, this business faces various obstacles, such as limited product diversification and production tools, as well as suboptimal use of digital marketing. These conditions have resulted in low production capacity and limited market access. This activity was carried out to address these problems by encouraging innovation in red ginger-based products while strengthening the digitalization of partner businesses. The purpose of this activity is to improve partner welfare through ginger product diversification, the application of technology in the production process, and the optimization of digital marketing to increase business competitiveness in the digital economy era. Implementation methods include socialization, training, technology application, mentoring and evaluation, which are carried out in a participatory manner with partners. The results of the activity implementation show a significant increase in several aspects of partner capacity. Knowledge of digital marketing strategies increased from 60% to 80%, readiness in utilizing production technology increased from 40% to 80%, while professional mindsets developed rapidly from 50% to 100%. Comparison of conditions before and after the activity indicates that participants not only gained additional conceptual insight, but also developed practical skills and demonstrated more modern and adaptive changes in attitudes in business management.